2010
DOI: 10.1007/s11199-010-9763-9
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Verbal Coercion Following Sexual Refusal During a Hookup: Diverging Gender Patterns

Abstract: This online study explored gender differences in affective reactions to sexual refusal during hookups and whether state or trait measures were the best predictors of verbal coercion. The Midwestern U.S. undergraduate sample included 220 men and 50 women previously in situations where they wanted more sexual contact than their heterosexual partner desired. Women reported stronger negative responses on several affect variables, suggesting that such refusals might have resulted in significant expectancy violation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 58 publications
3
21
0
Order By: Relevance
“…Unwanted sexual contact is often preceded by verbal coercion (Wright et al 2010). In one study of college women (Christopher 1988), 95 % reported being pressured into at least one unwanted sexual event, with several forms of coercion experienced prior to an unwanted event: 3.4 % had been pressured by explicit threats, 4.8 % by physical force, 35 % by deceptive promise and statements of affection ("sweet-talked"), and 55 % reported feeling pressured by behaviors that communicated an expectation of having sex (persistent attempts to initiate sexual activity).…”
Section: Unwanted Sexual Contactmentioning
confidence: 99%
“…Unwanted sexual contact is often preceded by verbal coercion (Wright et al 2010). In one study of college women (Christopher 1988), 95 % reported being pressured into at least one unwanted sexual event, with several forms of coercion experienced prior to an unwanted event: 3.4 % had been pressured by explicit threats, 4.8 % by physical force, 35 % by deceptive promise and statements of affection ("sweet-talked"), and 55 % reported feeling pressured by behaviors that communicated an expectation of having sex (persistent attempts to initiate sexual activity).…”
Section: Unwanted Sexual Contactmentioning
confidence: 99%
“…Men also were less likely than women to tell an unwanted pursuer directly they were "definitely not interested." Wright, Norton, and Matusek (2010) investigated responses to sexual refusals during actual heterosexual hookups by asking women and men about what coercive tactics they used in response to refusals, if any. Of the 773 women and 776 men who participated, more men (46%) than women (14%) of men reported having had at least one experience in the past year of wanting more sexual activity than their hookup partner.…”
Section: Interpersonal Scriptsmentioning
confidence: 99%
“…In contrast, women who felt rejected by a hookup partner were more likely to coerce than women who were embarrassed by the rejection. Additional research showed that, at times, both men and women attempt to verbally pressure and influence a reluctant partner to engage in unwanted sexual activity (O'Dougherty Wright et al 2010). However, women were far less likely than men to report having been in hookup situations in which they wanted more sexual activity than their partner.…”
Section: Interpersonal Scriptsmentioning
confidence: 99%
“…Van Wie and Gross (2001) also found that a partner's reason for rejecting sexual activity influenced men's ability to identify the refusal. In addition, men who were confused or angered by such a rejection were more likely to try to coerce their sexual partner into participating in the sexual activity (Wright, Norton, & Matusek, 2010).…”
Section: Sexual Assault and Negotiating Sexual Consentmentioning
confidence: 99%